2008
DOI: 10.1016/j.ijmultiphaseflow.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Atomization of viscous and non-newtonian liquids by a coaxial, high-speed gas jet. Experiments and droplet size modeling

Abstract: This paper describes a collaborative theoretical and experimental research effort to investigate both the atomization dynamics of non-Newtonian liquids as well as the performance of coaxial atomizers utilized in pharmaceutical tablet coating. In pharmaceutically relevant applications, the coating solutions being atomized are typically complex, non-Newtonian fluids which may contain polymers, surfactants and large concentrations of insoluble solids in suspension. The goal of this investigation was to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 19 publications
8
144
2
7
Order By: Relevance
“…This has been primarily due to the fact that the proposed models can not capture one other key feature, which is the saturation of the e↵ect at large values of the relaxation time. Previous analyses have argued that the droplet average size should be proportional to the wavelength of the final instability process during the atomization event, and a combination of linear stability analyses for the di↵erent instability modes in the air spray should predict the measured values for the mean droplet diameter < d > [2,89]. Although this scaling may work for inviscid jets, recent work by Marmottant and Villermaux [3] for viscous Newtonian fluids shows that the e↵ects of viscosity on the lifetime of the ligaments that form in the final stages of detachment from the core liquid jet play a dominant role in setting the average droplet size in the spray.…”
Section: E↵ect Of Extensional Properties On Atomizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been primarily due to the fact that the proposed models can not capture one other key feature, which is the saturation of the e↵ect at large values of the relaxation time. Previous analyses have argued that the droplet average size should be proportional to the wavelength of the final instability process during the atomization event, and a combination of linear stability analyses for the di↵erent instability modes in the air spray should predict the measured values for the mean droplet diameter < d > [2,89]. Although this scaling may work for inviscid jets, recent work by Marmottant and Villermaux [3] for viscous Newtonian fluids shows that the e↵ects of viscosity on the lifetime of the ligaments that form in the final stages of detachment from the core liquid jet play a dominant role in setting the average droplet size in the spray.…”
Section: E↵ect Of Extensional Properties On Atomizationmentioning
confidence: 99%
“…This limit can be circumvented by studying the dynamics of capillary breakup using the ROJER device because of the much smaller length and time This study helps us understand the subtle e↵ect of extensional rheology on the breakup and the atomization of weakly viscoelastic liquids which are widely used in many biological and industrial applications. For Newtonian liquids, two di↵erent scalings for ligament sizes are suggested based on linear stability analysis [89,91]. The di↵erence between the two scalings arises from the Rayleigh Taylor stability analysis, in which the direction of air acceleration relative to the liquid/air interface can change at di↵erent air/liquid flow rate ratios.…”
Section: Rayleigh-ohnesorge Jet Extensional Rheometer (Rojer) To Be mentioning
confidence: 99%
See 1 more Smart Citation
“…ese problems are particularly important for ultrafine coating due to its strict requirements. In order to solve these problems, the common practices are optimization design of the operating parameters such as adjustment of pressure, nozzle orifice, and gas-to-liquid flow ratio [8][9][10][11]. ese approaches can alleviate the uneven spray pattern, whereas the effect is limited and not essential to solve the above problems.…”
Section: Introductionmentioning
confidence: 99%
“…Dumouchel [10] has reviewed the experimental investigate dedicated to the primary atomization step for Newtonian liquids. Aliseda et al [11] extracted the images of liquid jet break-up which is closed to the nozzle orifice from high-speed visualizations for several Weber and Reynolds numbers for viscous and non-Newtonian liquids. They observed that at lower Weber numbers the Kelvin-Helmholtz instability grew slowly and several intact wavelengths were observed prior to break-up, In contrast at larger weber number, the Rayleigh-Taylor (R-T) instability was arresting.…”
Section: Introductionmentioning
confidence: 99%